Efficacy of whole-body vibration on balance and motor function in children with osteogenesis imperfecta: A randomized controlled trial - Hanady Abdallah Mouhamed; Nehad A. Abo-Zaid; Manal Mohammed Hassan; Mai Raouf Mohamed Rageh; Ayman M El Makaky; Shreen R Abdoelmagd; Eman Wagdy (Sport TK)
The current study aimed to examine the influence of whole-body vibration (WBV) on balance and motor function in children with osteogenesis imperfecta (OI). This randomized controlled trial (single-blinded) included forty children with OI, aged 8 to 13 years. Two groups with equal numbers were randomly selected; the control group received 40 min. standard program of physical therapy while the WBV group received the identical program as the control group for 20 min. plus 20 min. of WBV training. The program was carried out for all children twice weekly for three successive months. Biodex Balance System was utilized to evaluate the dynamic balance by measuring the stability indices and Gross Motor Function Measure was employed to evaluate the motor function for two groups, pre and post intervention. Following intervention, results showed statistically significant improvements in all evaluated outcomes of both groups, with the favor of WBV group (p< 0.05). Incorporating WBV training into a standard program of physical therapy has a greater effect on dynamic balance and motor function than a standard program of physical therapy only among children with OI.